ANALISIS PENGARUH PERSEPSI NASABAH BANK TERHADAP INTERNET BANKING ADOPTION (Studi pada Nasabah Perbankan yang Menggunakan Internet Banking di Kota Surakarta) - Nur Yudha, Hafid; Isgiyarta, Jaka (Diponegoro Journal of Accounting, 2015)
This study was conducted to analyze the factors affecting the banking customer to acceptance of Internet Banking Adoption. Results of this study are expected to contribute to banking institutions in order to enhance the credibility and increasing better service for customers who use Internet banking services, as well as provide multilevel security and update internet banking network system regularly that are not easily hijacked by the parties are not responsible. Samples were taken by cluster sampling method, which is based on the domicile of bank customers in five districts, in the city of Surakarta. These samples included 165 respondents. Testing method performed by multiple linear regression analysis were processed with SPSS for Windows version 19. Results of research conducted shows that the Perceived Ease of Use, Perceived Usefulness, Perceived Trust, and Computer Self-Efficacy provide a significant and positive effect on the acceptance of Internet Banking Adoption. While the perceived risk provides a significant and negative impact on the acceptance of Internet Banking Adoption. In a subsequent, study is expected to use a more diverse independent variables in predicting the effect on the dependent variable in order to obtain more specific results.